DIAGNOSIS OF THE LEVEL OF FORMATION OF CONSCIOUS PARENTHOOD OF STUDENT YOUTH AS A CONDITION FOR THE PREVENTION OF SOCIAL ORPHANHOOD - Kalchenko, Larysa; Ostrovska, Nataliya; Kuzmenko, Galyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article reveals the problem of the dependence of social phenomena – conscious parenthood and social orphanhood. The aim of the article is to present the results of experimental research in diagnosis of the level of creation of conscious parenting of student youth as a condition of prevention of social orphanhood in the territorial community of the city. The characteristic of the main components of the process of the formation of conscious parenthood of student youth is given, the essence of the phenomenon of social orphanhood is revealed. The main methods of this study are: methods of theoretical knowledge - analysis, synthesis, systematization, classification, generalization, focus groups, ranking method, survey methods - questioning, testing, socio-pedagogical experiment, monitoring, methods of mathematical statistics (Pearson's criterion χ2, Fisher criterion *F-test, Spearman's rank correlation coefficient). The results of the ascertaining and control stages of the experimental study on the diagnosis of the level of formation of the conscious parenthood of student youth in institutions of higher education in the cities of Lviv, Kyiv and Khmelnytsky (Ukraine) are presented.Diagnostic results of the ascertaining stage of the experiment has shown that the majority of modern Ukrainian students has a low level of knowledge and skills about conscious parenthood and they are practically not aware of the possibilities of the subjects of the territorial community of the city towards forming the youth conscious parenthood and preventing of the social orphanhood. At the formative stage of the experiment the strategy of involving and activating young students into the process of forming conscious parenthood through development and realization of social and pedagogical technology, aimed to popularization of the idea of conscious parenting among youth, is determined as a condition for precluding the Kalchenko et al., 2020.Диагностика уровня сформированности осознанного родительства студенческой молодёжи как условие превенции социального сиротства 288 phenomenon of social orphanhood, abandonment and homelessness of children. The results of the control phase of the experiment have confirmed the effectiveness of the developed and tested social-pedagogical technology and have shown a positive dynamics of changes in the level of formation of the conscious parenthood of students of the higher education institutions experimental groups for all indicators of cognitive and value-based behavioural criteria.